Value-Informed Public Service: Reframing Civic Professionalism for the 21st Century - Turner, Allison H. (Public Governance, Administration and Finances Law Review, 2025)
This paper introduces the concept of Value-Informed Public Service, emphasising the critical interrelationship between public service values, professionalism and information literacy in 21st century public administration. Using a conceptual analytical methodology, the study explores how public administrators operate in complex environments characterised by competing values and discretionary decision-making. Key findings highlight that effective public service requires integrating individual value orientations, professional standards and information literacy to guide context-specific decision-making while maintaining legitimacy with citizens and colleagues. The paper recommends institutionalising this integrated framework within public affairs education to prepare competent civic professionals. The originality of this study lies in bridging the theoretical and practical elements of these often separately acknowledged concepts, providing an enduring framework that advances both the scholarship and practice of public administration.